Clinical Profile, Severity Pattern and Socio-demographic Risk Factors of Acute Lower Respiratory Tract Infection (ALRTI) in Children in Enugu, Nigeria - Chinawa, Awoere; Chinawa, Josephat; Nduagubam, Obinna; Chukwu, Bartholomew; Nwokoye, Ikenna; Amadi, Oge; Ndu, Ikenna; Aronu, Ann; Eze, Joy (Current Respiratory Medicine Reviews, 2020)
Introduction: Acute lower respiratory tract infection (ALRTI) is a major public health problem that causes significant morbidity and mortality and is the main reason for utilization of health services among children. Objective: The study aimed to evaluate the clinical profile, severity pattern, and sociodemographic risk factors of ALRTI in hospitalized children under the age of five years in two tertiary hospitals in South East Nigeria. Materials and Methods: This is a cross-sectional study of children aged two months to five years in two teaching hospitals in the country. They were evaluated for ALRTI, focusing on their clinical profile and socio-demographic risk factors. Results: Two hundred children presented with features of ALRTI, mostly pneumonias and bronchiolitis. ALRTI occurred throughout the year with a peak in October. The majority had severe disease and risk factors for severity were infancy, type of ALRTI, presence of comorbidity and lack of measles vaccination or vitamin A supplementation, and exposure to wood smoke. Fast breathing was the most sensitive symptom, while breathlessness was the most specific for ALRTI. Conclusion: Bronchopneumonia and bronchiolitis are the most common ALRTI in under-five age children with bronchopneumonia occurring in severe forms. Poor breastfeeding, infancy, poor rate of immunization and exposure to biomass smoke are all risk factors for severity.
Keywords: socio-demographic risk factors